Смысл различения культуры и цивилизации - Возняк, Владимир (Східноєвропейський національний університет ім. Лесі Українки, 2016)
Смысл различения культуры и цивилизации состоит в том, что культура является порождающим основанием человеческого бытия, цивилизация – всего лишь условием. Культура – связь людей, цивилизация – сила вещей. Ориентация образования исключительно на цивилизационные измерения губительна для целостного развития личности. Если культура – порождающее основание, то именно она и должна учить и воспитывать, порождать и бережно хранить, оберегать человеческое в индивидах. Consideration of the concepts of «culture» and «civilization» as the similar ones ultimately leads to a reduction of culture to civilization and gives a background to ideological justification of the alienated state of the world of man. Culture is a founding background of the human existence; civilization is just its condition. According to F. T. Mikhailov concept, generating and preserving human relations is an appeal to the subjectivity of others in search of co-feeling, co-thinking, co-consent, and co-action with them. That is what provides the expanded reproduction of communities of people, creative, spiritual, and practical productivity of human existence. We can seek the ontology of culture as a vital connection and power of people. Civilization is a power of things. The distinction between culture and civilization is extremely important for the philosophical and educational discourse. Education oriented solely on the measurement of civilization is detrimental to the holistic development of the individual. If culture is founding background, it must teach, bring up, create and carefully preserve the human essence in the individuals.
Keywords: цивилизация; культура; порождающее основание; духовность культуры; образование; civilization; culture; founding background; culture spirituality; education